Exploring the adequacy of informed consent for caesarean section at a tertiary care center - V. P., Tejaswi; Dongare, Akshaya; Hegde, Prateeksha; Patil, G. L.; A. S., Shridevi; S., Anitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective was to study adequacy of valid informed consent in caesarean section and to quantify the proportion of patients who receive a proper informed consent before undergoing caesarean section. Methods: A cross-sectional questionnaire-based study involving 200 registered antenatal women undergoing caesarean section for various reasons both as elective or emergency basis, and data was analyzed. Results: Among the study group, 98.5% patients were informed about the said procedure in their own local language and consent was taken, in 3 (1.5%) patients informed consent was not taken. Detailed procedure was explained to only 29 patients (14.5%) whereas 171 patients (85.5%) had no clue about the detailed nature of the procedure. 193 patients (96.5%) were satisfied with the given informed patients; 7 patients (3.5%) were not satisfied. Conclusions: Women need consistent and adequate information for consent. Sessions should be held regarding the procedure, its risks and benefits; in this way patient will undergo the procedure with proper knowledge, awareness and confidence.